Aetiology Based Diagnosis and Treatment Selection in Intellectually Disabled People with Challenging Behaviours - Verhoeven, Willem M.A.; Egger, Jos I.M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Since both intellectual disability and challenging behaviour are entities encompassing heterogeneous clinical conditions and current taxonomies are of limited use in this field of psychiatry, diagnosing psychiatric symptoms in intellectually disabled patients is still very complex. In the diagnostic process of psychiatric symptoms and behavioural abnormalities, the first step should be genome profiling using the latest techniques in order to detect pathogenic CNVs or single gene mutations that are causative for the developmental delay. Their importance can be derived from the scientific observation that several genetic syndromes are associated with a specific behavioural, psychiatric, neuropsychological or neurological symptom profile, relevant for both choice of treatment and prognosis. Second, it has to be stressed that psychiatric disorders, especially from the depression and anxiety spectrum, frequently manifest with atypical symptoms that may hamper adequate pharmacological treatment. With respect to challenging behaviours in general, it should be emphasized that these are essentially dependent on contextual variables for which no rational pharmacological treatment is available and behavioural interventions are primarily warranted. Prescription of psychotropics has been demonstrated to be marginally effective only and to induce regularly unwanted side effects or even an increase of abnormal behaviours. It is therefore recommended to measure always the plasma concentration of psychotropics and antiepileptics and to perform, preferably prior to the start of treatment, genotyping of relevant cytochrome isoenzymes. In is concluded that, apart from the a priori genetic analysis, careful investigation of the here described data sources is needed to formulate a diagnostic hypothesis and treatment proposal.